PENGARUH PERUBAHAN INTENSITAS CAHAYA AKIBAT GERHANA MATAHARI SEBAGIAN TERHADAP GERAK DAUN Bauhinia purpurea - Alyasyfi, Muhammad Najib; Gusrianti, Dwi; Salam, Robby; Kurniawan, Rizky; Juliansyah, Fahmi; Nugraha, Muhamad Gina (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2016)
Solar eclipse is an event which occurs when sunlight travelling to earth was blocked by the Moon, causing the intensity of sunlight who reach the earth decreased. A change of intensity could affect the behaviour of certain plants, like Bauhinia purpurea. When it receives light, Bauhinia purpureaâ€™s leaves will opened up, when it receives no light, it will closed. The researchâ€™s objective is to learn the behaviour of Bauhinia purpurea during the eclipse. The observation was done in Bandung at the coordinate 107o35â€™24â€ E 6o51â€™36â€ S, May 9th 2016 when the partial solar eclipse occurs, started at 06:20:37 WIB until 08:32:37 WIB. The leaves movements was recorded with pocket camera, then analyzed with Tracker to obtain the width of leaves gap. The sunlight intensity was obtained by using Stellarium. The results shows that sunlight intensity when the solar eclipse started (0,002%/1384,044328 watt/m2) until it reached the maximum partial solar eclipse (85,9%/194,6032101 watt/m2) cause the leaves to closed up until 4,1 mm wide. While from the maximum until the eclipse is over (1384,044328 watt/m2), caused it to opened up until 5,0 mm wide. This results shows that the movement of Bauhinia purpureaâ€™s leaves was affected by the partial solar eclipse. Keywords: Eclipse, Intensity, Bauhinia purpurea.